VARIASI JUMLAH TUMBUKAN PADA PEMADATAN CAMPURAN BETON ASPAL MENGGUNAKAN BAHAN TAMBAH ANTI STRIPPING - Wiyono, Eko; Susilowati, Anni (Politeknik Negeri Jakarta, 2020)
AbstractThe objectives of the research were to obtain the Marshall properties of asphalt concrete mixture mixed with variations of manual compact collisions and to determine the optimum number of compactions collisions in the asphalt concrete mixture using anti stripping additives. The independent variables in this research are variation of the number of compaction collisions of asphalt concrete as many as 2x50, 2x75, 2x100, 2x125 and 2x150, with optimum asphalt content of 6%, and Wetfix Be 0,3% to optimum asphalt content. Marshall test method used in this research was based on SNI 06-2489-1991. The dependent variables (research parameters) included percent of cavities in the aggregate (VMA), percent of cavities in the mix, percent of cavities filled in asphalt (VFB), percent of cavity to mix (VIM), stability, melting, and Marshall Quotient. The result showed that the optimum number of compactions of asphalt concrete was 2x100 with Marshall properties value fulfilling SNI 8198-2015 specification. In Asphalt concrete mixture with optimum asphalt content (KAO) of 6%, Wetfix Be level of 0,3%, optimum number of compactions of 2X100, could be obtained by Aggregate (VMA) cavity 17.50%; Asphalt filled cavity (VFB) 76.50%; Cavity to Mixture (VIM) 4,00%; Stability of 1800.00 kg; Melting of 3.75 mm; and Marshall Quontient 500.00 kg/mmKeywords: Anti Stripping, Collision, Compaction, Wetfix BeAbstrakTujuan penelitian untuk mendapatkan nilai properties Marshall campuran beton aspal dengan berbagai variasi jumlah tumbukan pemadatan dan menentukan jumlah tumbukan pemadatan yang optimum pada campuran beton aspal dengan menggunakan bahan tambah anti stripping. Variabel bebas pada penelitian ini adalah variasi jumlah tumbukan pada pemadatan pembuatan beton aspalÂ sebanyak 2x50, 2x75, 2x100, 2x125 dan 2x150, dengan Kadar Aspal Optimum 6%, dan Wetfix Be 0,3% terhadap kadar aspal optimum. Metode pengujian Marshall berdasarkan SNI 06-2489-1991. Variabel terikat (parameter penelitian) meliputi persen rongga dalam agregat (VMA), persen rongga dalam campuran, persen rongga terisi aspal (VFB), persen rongga terhadap campuran (VIM), stabilitas, kelelehan, Marshall Quotient. Hasil penelitian didapat jumlah tumbukan pada pemadatan beton aspal yang optimum sebesar 2x100 dengan nilai properties Marshall memenuhi spesifikasi SNI 8198-2015. Campuran beton aspal dengan Kadar Aspal Optimum (KAO) 6%, kadar Wetfix Be sebesar 0,3%, Jumlah Tumbukan Optimum 2X100, diperoleh Rongga terhadap Agregat (VMA) 17,50%; Rongga Terisi Aspal (VFB) 76,50%; Rongga terhadap Campuran (VIM) 4,00%; Stabilitas 1800,00 kg; Kelelehan 3,75 mm; dan Marshall Quontient 500,00 kg/mmKata kunci: Anti Stripping, Tumbukan, Pemadatan, WetfixÂ Be